2000
DOI: 10.1023/a:1006403017578
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The technique of RT-PCR and restriction enzyme analysis was standardized to detect and differentiate Newcastle disease viruses. Digestion of RT-PCR-amplified, F gene sequences encoding for the cleavage activation sites of fusion protein with restriction enzymes AluI, BglI, HaeIII, HinfI, HhaI, RsaI, StyI and TaqI was carried out in order to characterize Newcastle disease viruses of varying pathogenicity. Restriction enzyme digestion of the amplicons by BglI and HhaI could group eight viruses, both field isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(20 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…Previously, several researchers reported methods for differentiating avirulent and virulent APMV-1 strains by simple REA using Bgl I [4,11]. We applied these methods to the APMV-1 strains used in this study, but the VG/GA vaccine strain was misidentified as a virulent strain (data not shown), as also suggested in a review by Cattoli [2].…”
mentioning
confidence: 78%
“…Previously, several researchers reported methods for differentiating avirulent and virulent APMV-1 strains by simple REA using Bgl I [4,11]. We applied these methods to the APMV-1 strains used in this study, but the VG/GA vaccine strain was misidentified as a virulent strain (data not shown), as also suggested in a review by Cattoli [2].…”
mentioning
confidence: 78%
“…The RT-PCR amplification of the partial fusion protein gene of the NDV revealed 1148 bp product for all the samples (Figure-6). RT-PCR technique has been routinely used for diagnosis of NDV and detecting NDV in clinical samples without necessitating virus isolation in ECE [13,14]. Singh et al .…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, a similar aPMV-1 strain was also described in India (UP2-92). This isolate from pigeons was characterised by a mesogenic ICPI but with an F protein cleavage site motif and restriction enzyme patterns typical of apathogenic vaccine strains [22,23]. The isolation of such strains highlights the importance of a better understanding of the virus pathogenesis in pigeons and the role that pigeons might be playing in the appearance or propagation of virulent strains of NDV.…”
Section: Discussionmentioning
confidence: 97%